Camasca, una ofrenda escénica en Amantaní, Puno (Perú) - Vargas Salgado, Carlos (2024)
This article discusses the generative elements of the project Camasca, a scenic gift in Amantaní (2024), starting from proposing the validity of the concepts of theater, aesthetics and epistemology when accounting for performative discourses present in festivities, rituals and similar, in the Andean world. The article at the same time discusses the Andean notions present in the original play, Camasca, as well as the function and value of oracles both in the past and as a veiled presence in our days. The text aims to share the general approach that the producers decided to put into practice, and it advances some theoretical conclusions about the Project.